Developing Audio-Visual EFL Material for Conditional Sentences - Marshanda Marshanda; Najwa Amalia; Rani Rani; Raysha Ramadhani; Zaitun Qamariah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study develops audio-visual teaching materials to enhance secondary school students’ understanding of conditional sentences in English as a Foreign Language (EFL) instruction. Adopting the Borg and Gall Research and Development (R&D) model, the study involves information gathering, planning, prototype development, field testing, and product revision. The materials include animated videos and interactive exercises designed to engage students and simplify complex grammatical concepts. Data collected through questionnaires, interviews, observations, and tests reveal improved student comprehension and engagement after using the materials. Teachers noted that these resources align with curriculum requirements and support effective grammar teaching. This study highlights the potential of audio-visual media in addressing challenges in EFL grammar instruction, offering practical and innovative solutions for educators.